2012
DOI: 10.1186/1471-2377-12-12
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of transcranial sonography in parkinson spectrum disorders in comparison to degenerative cognitive syndromes

Abstract: BackgroundHyperechogenicity of the substantia nigra (SN+), detected by transcranial sonography (TCS), was reported as a characteristic finding in Parkinson's disease (PD), with high diagnostic accuracy values, when compared mainly to healthy controls or essential tremor (ET) group. However, some data is accumulating that the SN + could be detected in other neurodegenerative and even in non-neurodegenerative disorders too. Our aim was to estimate the diagnostic accuracy of TCS, mainly focusing on the specificit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 37 publications
2
38
0
1
Order By: Relevance
“…(Von der Weid,2001; Langer et al,2002; Hill et al,2004; Spiegler et al,2006; Mahone et al,2007; Aukema et al,2009; Kadan-Lottick et al,2009; Kadan-Lottick et al,2010; Robinson et al,2010; Daams et al,2012; Krawczuk-Rybak et al,2012; Edelmann et al,2013; Genschaft et al,2013; Krull et al,2013; Lewis et al,2013; Ross et al,2013; Schuitema et al,2013; Edelmann et al,2014; Elalfy et al,2014) There were only 4 longitudinal studies that evaluated survivors’ neurocognitive changes from active treatment to post-treatment survivorship phase. (Kingma et al,2001; Harila et al,2009; Halsey et al,2011; Lewis et al,2013) Most studies focused on a pure sample of survivors who received chemotherapy-only treatment protocols while others included separate populations of ALL survivors who received CRT(Kingma et al,2001; Von der Weid,2001; Langer et al,2002; Spiegler et al,2006; Harila et al,2009; Kadan-Lottick et al,2010; Halsey et al,2011; Krull et al,2011; Daams et al,2012; Krull et al,2013; Schuitema et al,2013; Edelmann et al,2014) or patients of other cancer types.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Von der Weid,2001; Langer et al,2002; Hill et al,2004; Spiegler et al,2006; Mahone et al,2007; Aukema et al,2009; Kadan-Lottick et al,2009; Kadan-Lottick et al,2010; Robinson et al,2010; Daams et al,2012; Krawczuk-Rybak et al,2012; Edelmann et al,2013; Genschaft et al,2013; Krull et al,2013; Lewis et al,2013; Ross et al,2013; Schuitema et al,2013; Edelmann et al,2014; Elalfy et al,2014) There were only 4 longitudinal studies that evaluated survivors’ neurocognitive changes from active treatment to post-treatment survivorship phase. (Kingma et al,2001; Harila et al,2009; Halsey et al,2011; Lewis et al,2013) Most studies focused on a pure sample of survivors who received chemotherapy-only treatment protocols while others included separate populations of ALL survivors who received CRT(Kingma et al,2001; Von der Weid,2001; Langer et al,2002; Spiegler et al,2006; Harila et al,2009; Kadan-Lottick et al,2010; Halsey et al,2011; Krull et al,2011; Daams et al,2012; Krull et al,2013; Schuitema et al,2013; Edelmann et al,2014) or patients of other cancer types.…”
Section: Resultsmentioning
confidence: 99%
“…(Von der Weid,2001; Langer et al,2002; Hill et al,2004; Spiegler et al,2006; Mahone et al,2007; Aukema et al,2009; Kadan-Lottick et al,2009; Kadan-Lottick et al,2010; Robinson et al,2010; Daams et al,2012; Krawczuk-Rybak et al,2012; Edelmann et al,2013; Genschaft et al,2013; Krull et al,2013; Lewis et al,2013; Ross et al,2013; Schuitema et al,2013; Edelmann et al,2014; Elalfy et al,2014) There were only 4 longitudinal studies that evaluated survivors’ neurocognitive changes from active treatment to post-treatment survivorship phase. (Kingma et al,2001; Harila et al,2009; Halsey et al,2011; Lewis et al,2013) Most studies focused on a pure sample of survivors who received chemotherapy-only treatment protocols while others included separate populations of ALL survivors who received CRT(Kingma et al,2001; Von der Weid,2001; Langer et al,2002; Spiegler et al,2006; Harila et al,2009; Kadan-Lottick et al,2010; Halsey et al,2011; Krull et al,2011; Daams et al,2012; Krull et al,2013; Schuitema et al,2013; Edelmann et al,2014) or patients of other cancer types. (Aukema et al,2009; Kadan-Lottick et al,2010) The majority of the included studies had sample sizes between 10 to 50 subjects,(Kingma et al,2001; Langer et al,2002; Hill et al,2004; Mahone et al,2007; Aukema et al,2009; Harila et al,2009; Daams et al,2012; Krawczuk-Rybak et al,2012; Edelmann et al,2013; Genschaft et al,2013; Schuitema et al,2013; Edelmann et al,2014) with the exception of 4 studies with a larger cohort of more than 100 subjects(Von der Weid,2001; Kadan-Lottick et al,2010; Halsey et al,2011; Krull et al,2013) and 3 studies with less than 10 subjects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, hyperechogenicity of the SN on transcranial sonography (TCS) has been more frequently observed in patients with PD than in those with MSA or PSP [12, 13]. Taken together, these observations suggest that utilizing a combination of these batteries in addition to clinical assessment would be useful to achieve a correct diagnosis of PD.…”
Section: Introductionmentioning
confidence: 99%
“…The limitations of this method include dependence on the temporal acoustic bone window and low specificity, which would place it in the category of screening methods (10) . Some Brazilian studies have already confirmed the validity of TCS findings for the diagnosis of movement disorders among us (6,12) .…”
Section: Resultsmentioning
confidence: 99%